2010
DOI: 10.4038/cmj.v55i4.2627
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of intra-articular dexmedetomidine for postoperative analgesia in arthroscopic knee surgery

Abstract: Introduction Various drugs are administered intraarticularly to provide postoperative analgesia after arthroscopic knee surgery, of which opioids and alpha 2 agonists could be of particular interest. Methods Sixty patients undergoing elective knee arthroscopy were randomly assigned to two groups (n=30). Group R received 19 ml of 0.25% ropivacaine and 1 ml of isotonic saline (total volume 20 ml) intraarticularly. Group RD received 100 μg (1 ml) of dexmedetomidine added to 19 ml of 0.25% ropivacaine intra-articu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 17 publications
2
53
0
Order By: Relevance
“…The significant finding in our study was the increased VAS scores (Table 4) and the increased use of tramadol (Table 5) in the control group (group BS) as compared with the study group (group BD), at time intervals of 30 minutes, 1 hour, and 2 hours. These findings are consistent with the previous studies by Paul et al 6 and…”
Section: Resultssupporting
confidence: 94%
“…The significant finding in our study was the increased VAS scores (Table 4) and the increased use of tramadol (Table 5) in the control group (group BS) as compared with the study group (group BD), at time intervals of 30 minutes, 1 hour, and 2 hours. These findings are consistent with the previous studies by Paul et al 6 and…”
Section: Resultssupporting
confidence: 94%
“…Intraarticular dexmedetomidine in patients undergoing arthroscopic knee surgery improves the quality and duration of postoperative analgesia [29,30].…”
Section: Intraarticular Usementioning
confidence: 99%
“…[12] Paul et al concluded that intra-articular dexmedetomidine added as an adjunct to ropivacaine in patients undergoing arthroscopic knee surgery improved the quality and duration of postoperative analgesia. [13] Das et al in their study compared intraarticular ropivacaine ,fentanyl and dexmedetomidine for pain relief and suggested that ropivacaine was better than both fentanyl and dexmedetomidine. [14] Above studies confirm that intra-articular levobupivacaine dexmedetomidine combine can produce prolonged analgesia and require less rescue analgesic in comparison to ropivacaine dexmedetomidine combine.…”
Section: Resultsmentioning
confidence: 99%